Novel proapoptotic agent SM-1 enhances the inhibitory effect of 5-fluorouracil on colorectal cancer cells in vitro and in vivo - Wang, Ying (Oncol Lett, 2017)
5-Fluorouracil (5-FU) is one of the most important agents used to treat colorectal cancer. However, the therapeutic effect of 5-FU on colon cancer is limited. SM-1 is a novel type of proapoptotic agent that directly activates procaspase-3 to caspase-3, leading to apoptosis in human cancer cells. The aim of the present study was to evaluate the antitumor effects of 5-FU in combination with SM-1. The human colorectal cancer cell lines HCT116 and LoVo were cultured in the presence of SM-1 and 5-FU. The combination of SM-1 and 5-FU treatment exhibited increased proliferation inhibitory effects compared with 5-FU treatment alone in HCT116 and LoVo cells, as determined using an MTT assay. SM-1 significantly decreased the half-maximal inhibitory concentration of 5-FU from 8.07±0.49 to 2.55±0.41 µmol/l in HCT116 cells, and from 7.90±0.98 to 3.14±0.81 µmol/l in LoVo cells. Similarly, the apoptotic activity was increased to 47.95 and 35.19% in HCT116 and LoVo cells, respectively, as determined using Annexin V/propidium iodide staining and flow cytometry. The combination of SM-1 and 5-FU treatment led to significantly increased caspase-3 activity compared with either compound alone. The reverse transcription-quantitative polymerase chain reaction (RT-qPCR) and western blot analysis revealed the downregulation of B-cell lymphoma 2 and Survivin, and the upregulation of apoptosis regulator Bcl-2-associated X protein and cleaved poly (ADP-ribose) polymerase in HCT116 and LoVo cells. In addition, RT-qPCR identified downregulation of X-linked inhibitor of apoptosis protein mRNA. 5-FU and SM-1 treatment in combination increased tumor proliferation inhibition in HCT116 and LoVo xenograft mouse models of colorectal cancer, compared with SM-1 or 5-FU treatment alone. SM-1 significantly enhanced the antitumor activity of 5-FU in colorectal cancer. These improved effects were due to increased activity of the apoptotic signaling pathway.